Difusi Inovasi Kereta Kerakyatan melalui TikTok: Studi Kasus Akun @Keretaapikita - Deri Hanafy D; Rahmad Hidayat; Resna Wahyuni; Ike Junita Triwardhani (LPPM Universitas Adhirajasa Reswara Sanjaya, 2026)
ABSTRACT This study aims to analyze the role of TikTok as a communication medium for the diffusion of innovation related to the